A Review Study of Influencing Factors and Conceptual Scaling Framework for Spray Drying Assisted by Ultrasonic Vibrating Mesh Atomizers - Agustriputra IDG; Nata Septiadi Wayan; Dewa Ngakan Ketut Putra Negara; Tjokorda Gde Tirta Nindhia (Logic : Jurnal Rancang Bangun dan Teknologi, 2026)
Abstract. Spray drying is widely used in the pharmaceutical, food, and chemical industries for converting liquid feed into dry particulate products. However, conventional spray drying systems commonly generate broad droplet size distributions and exhibit limited capability for producing submicron particles. To overcome these limitations, ultrasonic vibrating mesh atomizers have recently attracted significant attention due to their ability to generate highly uniform droplets with relatively low energy consumption and improved atomization controllability. Previous studies have investigated the influence of individual operating parameters on ultrasonic spray drying performance, particularly using laboratory-scale systems such as the Büchi Nano Spray Dryer B-90. Nevertheless, existing literature remains fragmented, with limited efforts to systematically establish the relative importance of governing parameters or to develop a unified conceptual framework for scaling ultrasonic spray drying systems from laboratory to industrial applications. This study addresses this gap by conducting a systematic literature-based parametric analysis of spray drying systems assisted by piezoelectric vibrating mesh atomizers. Experimental studies employing the Büchi Nano Spray Dryer B-90 were critically reviewed to identify the dominant factors controlling droplet formation, atomization stability, and particle generation behaviour. The analysed parameters were classified into three principal categories: atomization parameters, fluid properties, and drying process parameters. The analysis demonstrates that mesh aperture size, ultrasonic vibration frequency, and spray throughput are the primary parameters governing droplet formation and particle size distribution. Fluid properties, including viscosity, surface tension, and feed concentration, strongly influence atomization stability through their effects on dimensionless parameters such as the Weber number and Ohnesorge number. In contrast, drying parameters, including inlet air temperature and gas flow rate, predominantly affect evaporation kinetics and particle morphology rather than the initial droplet generation process. The reviewed studies further indicate that ultrasonic atomization commonly operates within a regime characterized by moderate Weber numbers and relatively low Ohnesorge numbers, consistent with capillary wave breakup mechanisms. Based on these findings, a conceptual scaling framework is proposed in which atomization similarity, fluid dynamic similarity, and drying conditions must be simultaneously considered to achieve reliable scale-up of ultrasonic spray drying systems